How to measure experiences of healthcare quality in Denmark among patients with heart disease? The development and psychometric evaluation of a patient-reported instrument. Issue 10 (30th October 2017) - Zinckernagel, Line; Schneekloth, Nanna; Zwisler, Ann-Dorthe Olsen; Ersbøll, Annette Kjær; Rod, Morten Hulvej; Jensen, Poul Dengsøe; Timm, Helle; Holmberg, Teresa
Abstract : Objective: Measuring the quality of care as experienced by patients is increasingly recognised as a way of improving healthcare services. However, disease-specific measures that take the patient journey into account are needed. This paper presents the development of such a measure for patients with heart disease and details the psychometric evaluation. Design: The questionnaire was developed based on a literature review, qualitative interviews and a pilot-test. The psychometric evaluation of the measure was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), Cronbach's alpha coefficient and differential item functioning analysis with data from a population-based survey. Setting: Denmark in 2013–2014. Study participants: Nineteen heart patients, four relatives and eight health professionals participated in qualitative interviews in the development phase, and 15 patients participated in the pilot-test. The questionnaire was subsequently sent to a random sample of 5000 heart patients who were diagnosed in 2013. Results: The comprehensive development phase and pilot-testing contributed to high content validity of the questionnaire. Eligible questionnaire responses were received from 2496 patients. EFA indicated a nine-factor model: communication at the hospital, communication with the general practitioner, information on disease and treatment, information on psychosocial aspects, rehabilitation/support, organisation, medication, involvement of relatives and consideration of comorbidity. CFA confirmed the proposed factor structure (eg, goodness-of-fit index=0.88, adjusted goodness-of-fit index=0.86, root mean square error of approximation=0.05), and Cronbach's alpha coefficient revealed good internal consistency of the factors (range: 0.69–0.93). Conclusions: The results suggest that this disease-specific patient-reported experience measure is of good quality when measuring the quality of care among heart patients. The inclusion of patients in the development phase contributed to high content validity, and subsequent psychometric evaluation found high construct validity and internal consistency. This measure may be especially relevant when seeking information about which aspects of care require improvement and the impact on health outcomes.